Studi Literatur Pemikiran Ekonomi Islam Al-Ghazali: Relevansinya Terhadap Dinamika Ekonomi Global Saat Ini - Divia Inge Salsabila; Prames Wary Tri Wulandari; Khairida Nur Rahmah; Alifian Aiman (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2025)
Abstract This study examines the relevance of Imam Al-Ghazali’s economic thought in addressing modern economic challenges through a descriptive qualitative approach and literature review. By analyzing 30 scholarly publications from the SINTA database, this research highlights Al-Ghazali’s comprehensive contribution to Islamic economics, encompassing spiritual, ethical, and social dimensions. Core concepts such as maslahah (social welfare), distributive justice, the strategic role of the state, and business ethics serve as foundational pillars in constructing an economic system that is grounded not only in legality but also in divine values. The findings reveal that Al-Ghazali’s Sufi approach effectively harmonizes sharia and inner spiritual truths (haqiqah) within economic practice, framing economic activity as a form of worship and social responsibility rather than mere profit-seeking. The relevance of his ideas is reflected in contemporary instruments such as zakat, sukuk, and the just management of public finance. This study underscores the importance of internalizing spiritual values in the formulation of Islamic economic policies to achieve both barakah (divine blessing) and social sustainability.  Abstrak Penelitian ini mengkaji relevansi pemikiran ekonomi Imam Al-Ghazali dalam menghadapi tantangan ekonomi modern melalui pendekatan kualitatif deskriptif dan kajian pustaka. Dengan mengkaji 30 publikasi ilmiah dari basis data SINTA, penelitian ini menyoroti kontribusi Al-Ghazali terhadap ekonomi Islam secara menyeluruh, meliputi aspek spiritual, etika, dan sosial. Konsep maslahah (kesejahteraan sosial), keadilan distributif, peran strategis negara, dan etika bisnis menjadi fondasi utama dalam membangun sistem ekonomi yang tidak hanya berlandaskan pada legalitas, tetapi juga pada nilai-nilai ketuhanan. Temuan penelitian menunjukkan bahwa pendekatan sufi Al-Ghazali mampu menyelaraskan syariah dan hakikat dalam praktik ekonomi, menjadikan aktivitas ekonomi sebagai bentuk ibadah sekaligus tanggung jawab sosial, bukan sekadar alat untuk meraih keuntungan. Relevansi gagasannya tercermin dalam instrumen kontemporer seperti zakat, sukuk, dan pengelolaan keuangan publik yang berkeadilan. Penelitian ini menekankan pentingnya internalisasi nilai-nilai spiritual dalam formulasi kebijakan ekonomi Islam guna mewujudkan keberkahan dan keberlanjutan sosial.